Dielectric and piezoelectric properties of Sr doped 0.8PZT-0.2PNN ceramics - K. Sutjarittangtham (2018)
The solid solution of 0.8(Pb(Zr1/2Ti1/2)O3) - 0.2(Pb(Ni1/2Nb2/3)O3) doped with Sr were prepared by solid state route. Effect of Sr dopant on dielectric and piezoelectric properties was investigated. The dielectric constant at room temperature of the ceramics was found to increase with increasing Sr concentration. An increase in tunability was observed for the samples doped with higher Sr concentration. However, the maximum piezoelectric coefficient (d33) was observed for the ceramic doped with 0.6 mol% Sr. Copyright © Taylor & Francis Group, LLC.